Using tools effectively despite defective hand posture: A single-case study. (August 2020) - Lesourd, Mathieu; Naëgelé, Bernadette; Jaillard, Assia; Detante, Olivier; Osiurak, François
Abstract: Apraxia, a cognitive disorder of motor control, can severely impair transitive actions (object-related) and may lead to action errors (e.g., rubbing a hammer on a nail instead of pounding it) and hand posture errors (e.g., grasping a tool in a wrong way). Here, we report a rare observation of a left-handed patient, left-lateralized for language, who developed a severe apraxia following a right brain lesion. Interestingly the patient showed a significant number of hand posture errors, while she perfectly demonstrated the actual use of tools. This case stressed the predictions made by the current theories of tool use. According to the manipulation-based approach, the hand posture errors should be associated with an impaired manipulation knowledge. According to the reasoning-based approach, the absence of action errors should be associated with spared mechanical knowledge. Moreover, to better understand the neurocognitive origins of the deficit observed in VF, we examined several potential brain lateralization of praxis functions. We initiated a systematic examination of VF's performance in several contexts of tool use allowing us to investigate which kinds of tool-use representations were potentially impaired in VF. Our investigation did not reveal any major deficit of manipulation knowledge. This can hardly account for the high frequency of hand posture errors, contrary to the predictions of the manipulation-based approach. In contrast, in line with the reasoning-based approach, mechanical knowledge was spared and can explain the absence of action errors. We also found that VF probably had a bilateral organization of praxis functions, but irrespective of the possible brain lateralization considered, none of which established a satisfactory association between manipulation knowledge and hand posture errors. Taken together, the manipulation-based approach fails to explain fully the deficit presented by this patient and should lead us to consider alternative explanations.